Advances in management accounting. Vol. 27 - Epstein, Marc J.; Malina, Mary A. (Emerald, 2016)
Advances in Management Accounting publishes thoughtful, well-developed articles across a broad spectrum of current topics in the field of management accounting, using a variety of research methods including survey research, field tests, corporate case studies and modeling. Volume 27 exemplifies the broad scope of Advances in Management Accounting, examining a number of areas within management accounting.
Keywords: Business & Economics -- Accounting -- Managerial.; Management accounting & bookkeeping.; Accounting.; Managerial accounting.; elektronické knihy; electronic books